Investigation of intermolecular interactions between [Ho(H2O)8]4+ based 3D metal-organic supramolecular host and bipyridyl guest through crystal structure and Hirshfeld surface analysis. Issue 11 (3rd June 2021) - Patra, Maxcimilan; Dubey, Soumen Kumar; Singha, Soumen; Rizzoli, Corrado; Bhattacharjee, Subham; Saha, Rajat
Abstract: A new supramolecular metal-organic complex 1, [Ho(H2 O)8 4+ (TBTA)(bipy)] (where H2 TBTA = tetrabromoterephthalic acid and bipy = 4, 4'-bipyridyl), has been synthesized hydrothermally at 100 °C by mixing the reactants in stoichiometric ratio. The complex was characterized by single crystal X-ray diffraction (SC-XRD) along with powder X-ray diffraction (PXRD) and other spectroscopic analyses. Structural analysis reveals that 1 crystallized in the tetragonal space group I4cm and is a mononuclear complex. Ho 4+ presents octa-coordinated square antiprism geometry having eight coordinated water molecules. Hydrogen bonding interactions between the coordinated water molecules and carboxylate oxygen atoms of TBTA (doubly deprotonated form of H2 TBTA) anions form 3D supramolecular metal-organic host (MOSH) having 2D square grid-like supramolecular channels. Guest bipy molecules get stability within the channels through supramolecular π···π interactions between the bipy and TBTA anions. Hirshfeld surface analysis and corresponding 2D fingerprint plots correlate with the experimental findings. C···C short contact, corresponding to π···π interactions, contributes around 10.7% to the total surface. Abstract :